Temporal and spatial pattern analysis of pharyngeal swallowing in patients with abnormal sensation in the throat - Saito, K (Nippon Jibi Inkoka Gakkai Kaiho, 1995)
There are many patients who complain of abnormal sensations, such as an obstructive sensation, foreign body sensation, difficulty in swallowing, etc., in the throat, which do not have an obvious cause. The causes of such unpleasant symptoms have not been adequately investigated. As one of the potential factors in volved in abnormal sensations in the throat, we considered the existence of subclinical dysphagia. We then performed videofluoroscopic analysis in patients with an abnormal sensation in the throat to examine whether or not there were functional disorders in swallowing. Videofluoroscopy was performed in 42 subjects, 30 patients with abnormal sensation in the throat and 12 volunteers without swallowing problems. We devised a temporal and spatial analysis system of swallowing using personal computer technology. Videofluoroscopic swallowing sequences during spoon feeding (3-5ml) and drinking from a cup (15-20ml) of liquid barium, were analyzed. The results suggest that two temporal measurements of swallow from videofluoroscopic studies are appropriate for parameter of subclinical dysphagia: the time it takes the bolus to move through pharynx from the point at which the bolus head passes the tongue base until the bolus head extends caudally beyond the piriform sinus while feeding from a spoon (S2), and the time it takes the bolus to move through the upper esophagus from the point at which the bolus head passes the bottom of the piriform sinus until the bolus tail passes the same point while drinking from a cup (C1). Then, we selected C1 and S2 for variables and detect the patients who have subclinical dysphagia with cluster analysis. Forty-two subjects were divided into two groups: those composed of 14 patients (cluster 1), and those composed of 16 patients and 12 controls (cluster 2). We thought 14 patients in cluster 1 would have subclinical dysphagia for the cause of abnormal sensation in the throat. Temporal and spatial analysis revealed three forms of pharyngeal swallow in cluster 1. In 6 patients, the bolus stall in the valleculae prior to the onset of the pharyngeal swallow. In other 6 patients, the bolus stall in the piriform sinus before swallowing reflex. In the other 2 patients, the bolus moved smoothly but slowly without delay in pharynx. Our results indicate that a delayed swallowing reflex is the main functional finding in videofluoroscopy in patients with subclinical dysphagia contributing to an abnormal sensatin in the throat.